Особливості формування Т-залежних зон селезінки після внутрішньоутробної дії антигенів - Апт, Ольга Анатоліївна; Apt, O. A. (My University, 2014)
У роботі вивчені особливості морфогенезу морфофункціональних зон білої пульпи селезінки білих щурів у різні терміни після народження в нормі та після внутрішньочеревного введення антигенів. Встановлено, що процес формування зон білої пульпи має стадійний характер; внутрішньочеревне введення антигенів різної природи призводить до змін в темпах становлення морфофункціональних зон білої пульпи та динаміці їх клітинної популяції. Незалежно від типу антигену після народження спостерігається прискорення формування внутрішньої зони періартеріальних лімфоїдних муфт та стінки центральної артерії. В работе исследованы oсобенности строения морфофункциональных зон белой пульпы селезёнки белых крыс в разные сроки после рождения в норме и после внутриутробной антигенной стимуляции. Установлено, что процесс становления морфофункциональных зон белой пульпы носит стадийный характер. Внутриутробное введение антигенов вызывает изменения в темпах формирования таких зон и динамике их клеточной популяции. Независимо от вида внутриутробно введенного антигена, после рождения наблюдается ускорение формирования внутренней зоны периартериальных лимфоидных муфт и стенки центральной артерии. This research was made, using 168 rats of Wistar line in the age from 0 to 30 days. For the investigation were applied morphological, morphometrical, histological methods. This work describes peculiarities of rat’s splenic white pulp, morphofunctional zones structure attached to different terms after the birth normally and after intrauterine injection of human immunoglobulin and alive paroties vaccine. It’s established that intrauterine injection of antigens with different nature leads to the megalosplenia development. It’s noted that formation process of morphofunctional zones of white pulp has a stagical character. It had been shown that after the birth acceleration of inner periarterial lymphoid sheathes and central artery wall formation is occurred independently of intrauterine injected antigen type. The dynamics of the growth of the white pulp divisions depends on the prenatal antigen stimulation: it changes the terms of the development of morphofunctional zones of the splin, varies relationship between microenvironment and different groups of lymphocytes. Prenatal antigen stimulation leads to increase of the contents of middle and small lymphocytes and decrease of amount of large lymphocytes in the newborn PALS. The development of morphofunctional zones of the splin has the same dynamics up to the 5-th day of rat`s life independently of the antigen`s type. The changes of content of the lymphocytes in the morphofunctional zones were determined after 7-th day of the experimental animals`life.
Features of T-dependent zone of spleen formation after intrauterine antigens injection
Keywords: селезінка; біла пульпа; періартеріальна лімфоїдні муфта; морфогенез; внутрішньочеревне введення антигенів; селезёнка; белая пульпа; периартериальная лимфоидная муфта; внутриутробное введение антигенов; spleen; white pulp; periarterial lymphoid sheathes; morphogenesis; intrauterine antigens injection